2006
DOI: 10.1590/s0074-02762006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adenosine deaminase seric activity in the diagnosis of bovine tuberculosis

Abstract: Determination of seric levels of adenosine deaminase (ADA), an enzyme produced by monocytes/macrophages and lymphocytes, has been used in the diagnosis of human tuberculosis (TB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
5
1
2
Order By: Relevance
“…Missing data were not considered in the Chi-square test for these comparisons, in accordance with previous studies. 24 , l…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Missing data were not considered in the Chi-square test for these comparisons, in accordance with previous studies. 24 , l…”
Section: Methodsmentioning
confidence: 99%
“…Data on the TB status in Juiz de Fora are provided by the Municipal Secretariat of Health or found in scientific publications. 24 , 25 , 27 , f , h Furthermore, issues related to TB control remain unresolved: Does the treatment default rate in Juiz de Fora exceed the rate recommended by MS? Is the actual treatment default rate higher than the one reported to SINAN by the municipality?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of the sensitivity of tuberculin test range from 68-95% while specificity is estimated to be 96-99% (Monaghan et al 1994), and in the present study the sensitivity of SICTT was 24/30 (80%). Silva et al (2006) compared the seric levels of adenosine diaminase (ADA) to SICTT results during diagnosis of bovine TB, but the authors reported the impossibility to establish a meaningful cutoff for ADA seric values, concluding that the latter in its present form is of no use as an auxiliary test for diagnosis of bovine TB.…”
Section: Isolation and Identification Of Bovine Tuberculosis In A Bramentioning
confidence: 99%
“…Its activity has been reported in several diseases, including AIDS in humans, and is even considered to be an auxiliary diagnostic tool in some diseases such as tuberculosis [4,7]. In animals, total ADA activity is elevated in bovine leukosis [31], liver diseases [1], tuberculosis [26] and canine liver disease [3].…”
mentioning
confidence: 99%